1992
DOI: 10.1136/gut.33.9.1239
|View full text |Cite
|
Sign up to set email alerts
|

Faecal unconjugated bile acids in patients with colorectal cancer or polyps.

Abstract: The unconjugated faecal bile acid profiles of 14 patients with colorectal cancer, nine patients with polyps and 10 controls were compared using gas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(60 citation statements)
references
References 50 publications
0
60
0
Order By: Relevance
“…One of the most predominant secondary bile acids is deoxycholic acid, which is a cancer-promoting substance as demonstrated in rats by its ability to increase proliferation of colonic crypt cells [8] and potentiate the stomach tumorigenic effect of the chemical carcinogen, N-methyl-N'-nitro-N-nitrosoguanidine [9]. The notion that deoxycholic acid and other secondary bile acids contribute to the development of colon cancer is supported by the finding that elevated levels of secondary bile acids are present in the colon residual fluid or fecal material of human subjects with colon cancer [10].…”
Section: Introductionmentioning
confidence: 54%
“…One of the most predominant secondary bile acids is deoxycholic acid, which is a cancer-promoting substance as demonstrated in rats by its ability to increase proliferation of colonic crypt cells [8] and potentiate the stomach tumorigenic effect of the chemical carcinogen, N-methyl-N'-nitro-N-nitrosoguanidine [9]. The notion that deoxycholic acid and other secondary bile acids contribute to the development of colon cancer is supported by the finding that elevated levels of secondary bile acids are present in the colon residual fluid or fecal material of human subjects with colon cancer [10].…”
Section: Introductionmentioning
confidence: 54%
“…Although the secondary acid compounds may promote the growth of colonic adenomas from which adenocarcinomas may eventually arise (106), epidemiological studies of humans have been conflicting. Some case-control studies have found increased levels of fecal or serum bile acids in patients with colorectal adenomas or cancer (21,22,119,201), whereas others have not (105,170,171). The studies have varied significantly in methodology, choice of controls, the type of bile acid measured (primary, unconjugated, secondary, deoxycholate, etc.…”
Section: Toxic Bacterial Metabolitesmentioning
confidence: 99%
“…Although BAs are essential for lipid absorption, high concentration of BAs is linked to increased colon tumorigenesis (2,17,27). Indeed, patients with colorectal cancer increased fecal BA excretion (11,43).…”
mentioning
confidence: 99%